2012
DOI: 10.5505/tjh.2012.72623
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral exudative retinal detachment as the sole presentation of relapsing acute lymphoblastic leukemia

Abstract: Ocular findings are rarely the initial symptom of leukemia, although up to 90% of all leukemia patients have fundus changes during the course of the disease. Herein we report a relapsing acute lymphoblastic leukemia patient with thesole presentation of sudden visual loss and exudative retinal detachment. An 8-year-old boy with acute lymphoblasticleukemia developed sudden visual loss during his first remission period. Bullous retinal detachment with total afferentpupillary defect was observed. Orbital magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…Patient was treated with prednisolone, topical steroid and atropine but while when she administered her CSF and bone marrow was clean, after five months bone marrow relapse was seen (5). In our country, Azık et al (6) reported an eight-year-old ALL patient, who had sudden visual loss in remission period. In this case there was also isolated orbital relapse was detected without bone marrow and central nervous system relapse.…”
Section: Discussionmentioning
confidence: 95%
“…Patient was treated with prednisolone, topical steroid and atropine but while when she administered her CSF and bone marrow was clean, after five months bone marrow relapse was seen (5). In our country, Azık et al (6) reported an eight-year-old ALL patient, who had sudden visual loss in remission period. In this case there was also isolated orbital relapse was detected without bone marrow and central nervous system relapse.…”
Section: Discussionmentioning
confidence: 95%
“…We present a case of unilateral leukemic infiltration as the sole manifestation of relapsed ALL-B. Though, infrequent, unilateral eye involvement as the first sign of leukemic relapse has been described previously in the literature [ 2 ], [ 5 ], [ 6 ], [ 7 ]. Our patient presented with an intraocular mass occupying the entire vitreous cavity with associated vitreous hemorrhage and choroidal detachment.…”
Section: Discussionmentioning
confidence: 98%
“…Ischemia-induced dysfunction of Bruch's membrane and the retinal pigment epithelium leads to retinal detachment. Aside from pre-T-ALL, other causes of retinal detachment include central serous chorioretinopathy, choroidal melanoma, choroidal neovascularization, congenital optic disc pits, Harada's syndrome, uveal effusion syndrome, severe ocular hypotony, cardiac disease, and renal dysfunction [ 7 , 8 ]. In our case, these causes were excluded by the patient's history and ocular presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Azik et al [ 8 ] described a third case, an 8-year-old boy with a history of pre-B-ALL who presented with unilateral vision loss and exudative retinal detachment of the left eye with a subretinal mass. The patient did not undergo biopsy to confirm the diagnosis but rather received local radiotherapy and systemic and intrathecal chemotherapy with resolution of the mass.…”
Section: Discussionmentioning
confidence: 99%